1979
DOI: 10.1126/science.432659
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Fibroblasts Derived from Papillary and Reticular Dermis: Differences in Growth Potential in Vitro

Abstract: Papillary fibroblasts, when compared to reticular fibroblasts from the same skin specimen, exhibit greater proliferative capacities in vitro. These results demonstrate a difference in function between morphologically similar cells obtained from the same tissue. Such findings represent an important consideration in the study of cell aging in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(139 citation statements)
references
References 7 publications
10
126
1
2
Order By: Relevance
“…Differences are reproducible between passages 4 and 9, suggesting that the level of collagen synthesis is conserved through multiple cell population doublings and is a heritable and intrinsic property of the cell. Recently recognized differences between papillary and reticular dermal fibroblasts in normal (9) and scleroderma (6,lO) skin may represent in vivo segregation of heterogeneous dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Differences are reproducible between passages 4 and 9, suggesting that the level of collagen synthesis is conserved through multiple cell population doublings and is a heritable and intrinsic property of the cell. Recently recognized differences between papillary and reticular dermal fibroblasts in normal (9) and scleroderma (6,lO) skin may represent in vivo segregation of heterogeneous dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are cells that synthesize and integrate structural proteins such as collagen and elastin into the extracellular matrix (ECM) of most mesenchymal tissues (1)(2)(3)(4). It has long been believed that fibroblasts exhibit differing functional identities (5), and in recent years, evidence has emerged to support this concept. Fibroblasts are characterized by the expression of markers including vimentin and procollagen Iα2 chain (1).…”
Section: Introductionmentioning
confidence: 98%
“…Papillary and reticular fibroblasts can be isolated by explant culture of mechanically sectioned (dermatomed) human dermis. Explant fibroblast cultures derived from these layers exhibit differences in a number of parameters, including rate of cell division, contraction, and the expression of various collagens and proteoglycans (5,51,52). Cultured fibroblasts derived from the papillary dermis support the formation of a normal stratified epidermis in three-dimensional organotypic culture more effectively than fibroblasts from the reticular dermis (47,53,54).…”
Section: Fibroblast Heterogeneity According To Anatomical Originmentioning
confidence: 99%
“…Dermis fibroblasts might be the candidate which involve the disturbance of glycosaminoglycan metabolism in scleroderma. Harper and Grove (10) reported that papillary fibroblasts, when compared to reticular fibroblasts from the same skin specimen, exhibit greater proliferative capacities in virro. Tajima er al.…”
Section: G/ycosam1'1-tog/ycan Synthesis By Skin Ciilmrementioning
confidence: 99%